Exploring Non-pharmacological Methods for Pre-operative Pain Management - Patil, Jayaditya Devpal; Sefen, Jessica Atef Nassef; Fredericks, Salim (Frontiers in Surgery, 2022)
The management of pain is an essential aspect of surgical care, and pain levels in post-operative patients vary case by case. Treating postoperative pain is crucial as it leads to better outcomes and reduces risk of long term pain. While postoperative analgesics has been the mainstay of treatment, this mini-review explores an emerging concept which is preoperative pain management, with promising potential. Such interventions include educating patients on the expected pain outcomes and available pain medications. Non-pharmacological methods such as relaxation exercises have also proven to be effective after abdominal surgery, and educating patients on the existence of such methods pre-operatively encourages them to make use of available therapies. A major area of importance is the pre-operative psychological and emotional wellbeing of patients, as it is a strong predictor of pain and pain prognosis. Cognitive Behavioral Therapy can be effectively used to tackle preoperative anxiety and reduce pain levels. Hypnosis is another developing modality for decreasing stress. Lastly, long term pre-operative opioid use has been linked with higher pain scores and longer pain duration. This provides the basis on which pre-operative opioid weaning can lead to favorable post-operative pain outcomes. While many of these methods have not been experimented on recipients of abdominal surgery in specific, it still paves the path for newer pain control strategies that can eventually be adopted for visceral surgery patients. This review points the reader and researchers to new and developing areas that hold the potential to revolutionise current established pain management guidelines.